Validation of cone-beam computed tomography as a predictor of osteoporosis using the Klemetti classification - Maria Beatriz Carrazzone Cal ALONSO; Taruska Ventorini VASCONCELOS; Luciana Jácome LOPES; Plauto Christopher Aranha WATANABE; Deborah Queiroz FREITAS (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract This study aimed at evaluating the validity of cone-beam computed tomography (CBCT) for assessing mandibular bone quality using the Klemetti classification. The morphology of the endosteal mandibular cortex of 30 (60 hemi-mandibles) postmenopausal women between the ages of 45 and 80 years was evaluated based on the Klemetti classification in panoramic radiographs used as reference images. Afterwards, panoramic reconstruction and cross-sectional slices of CBCT examinations of these patients were analyzed and categorized according to the same classification. All the images were assessed by two oral radiologists. The McNemar-Bowker test compared the agreement between the CBCT images and the reference images. No differences were found between the diagnostic results based on panoramic radiography and panoramic reconstruction. However, the mean scores for the cross-sectional evaluation were higher, and the results, statistically different from the others. Based on the disagreement found between the panoramic radiographs and the CBCT cross-sectional slices, the Klemetti classification is not an adequate means of assessing bone quality with CBCT. On the other hand, the higher values found for the cross-sectional slices could be associated with better visibility on the CBCT images.